2012
DOI: 10.1007/s10943-012-9667-9
|View full text |Cite
|
Sign up to set email alerts
|

Religious Commitment, Attitudes Toward Suicide, and Suicidal Behaviors Among College Students of Different Ethnic and Religious Groups in Malaysia

Abstract: The variation in suicide patterns across ethnic groups with different religious background is a puzzling social phenomenon. This study sought to examine the impact of religious commitment and attitudes toward suicide on suicidal behaviors of college students across major ethnic and religious groups in a multicultural society of Malaysia. A total of 139 college students completed Religious Commitment Inventory-10, Attitudes Toward Suicide Scale, and Suicidal Behavior Questionnaire-Revised. Findings showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
2
33
0
1
Order By: Relevance
“…The results from the current study are consistent with Chia’s [26], who reported that a risk factor for young Chinese is mental illness, and congruent with the prevalence of a prior mental illness for suicide deaths in Singapore [50]. They also do not have religious beliefs with strong sanctions against suicide, consistent with a review of recent literature showing that religion is a common purveyor of cultural sanctions regarding the acceptability of suicides [5152]. …”
Section: Discussionsupporting
confidence: 90%
“…The results from the current study are consistent with Chia’s [26], who reported that a risk factor for young Chinese is mental illness, and congruent with the prevalence of a prior mental illness for suicide deaths in Singapore [50]. They also do not have religious beliefs with strong sanctions against suicide, consistent with a review of recent literature showing that religion is a common purveyor of cultural sanctions regarding the acceptability of suicides [5152]. …”
Section: Discussionsupporting
confidence: 90%
“…Malaysia is one of the Islamic countries with the Muslims population approximately 60.4 % of the total population (Foo et al 2014). Suicide is a horrible crime under Islamic law in Malaysia, and suicide attempts may lead to criminal prosecution.…”
Section: Introductionmentioning
confidence: 99%
“…While the Australian respondents thought Alex would attempt suicide, in Brazil respondents thought Alex would seek help from a trusted confidential source (e.g., a medical professional, or a religious person). It has been proposed that religious individuals might intervene (e.g., ministry of intercession) to increase suicidal individuals' feeling of belongingness [54,55]. Therefore, it is plausible that respondents from Brazil, a highly religious nation [56], are more likely to believe that Alex would seek help, especially from a religious person.…”
Section: Discussionmentioning
confidence: 99%